Analysis of a Modern Myth: The Star Trek Series. - Ellington, Jane Elizabeth; Critelli, Joseph W. (Extrapolation (Kent State University Press))
Argues that the unusual appeal of the television series "Star Trek," indicates that it carries the numinous quality of a modern myth. Jungian theory for the understanding of the purpose and significance of art; Application of Jung's type system to "Star Trek"; Universality of Jungian symbols; Jung's description of active fantasy; Argument that as a result of both biological and social factors, people develop a preference for consciously dealing with the world in terms of one pole of an attitude or function rather than its opposite;